Investigation of Prunus domestica Leaves Aqueous Extracts as a Sustainable Solution for Corrosion Control of Carbon Steel in 1M HCl: Thermodynamic, Adsorption and Electrochemical Insight - Akatyev, Nikolay; Khapiyeva, Meruyet; Kenzhegalieva, Roza; Talapova, Aruzhan; Uzakbay, Gauhar; Tlektes, Aikorkem; Logashkina, Alexandra (Journal of Science and Technology, 2025)
This study investigates the efficacy of Prunus domestica leaves aqueous extract (PDLAE) as a sustainable corrosion inhibitor for carbon steel in 1M hydrochloric acid solution. The research aligns with green chemistry principles, addressing the environmental concerns associated with the use of synthetic inhibitors. Comprehensive analyses, including weight loss assays, electrochemical measurements, adsorption isotherms, contact angle determination, and UV-visible spectroscopy, were conducted to evaluate the extract's corrosion inhibiting performance. The results revealed that the extract achieved a maximum inhibition efficiency of 92.07% at 2.0 g·dm?³ concentration after 24 hours, with thermally stable adsorption observed at high temperatures. Adsorption obeys the Langmuir model, indicating monolayer formation, and negative Gibbs free energy values (?G0ads ?-20 kJ·mol-1) confirm spontaneous adsorption. Electrochemical tests demonstrated mixed-type inhibition behavior, reducing corrosion current density and enhancing charge transfer resistance. Additionally, the extract improved surface hydrophobicity, as evidenced by increased contact angles. FTIR analysis identified the presence of key phytoconstituents bearing hydroxyl and carbonyl functional groups and aromatic structures that contribute to corrosion inhibition efficiency. Obtained results highlight the PDLAE's potential as an eco-friendly and effective solution for metal protection and the importance of plant-based inhibitors in advancing environmentally benign corrosion prevention strategies.